FIDEVELOPMENT OF STUDENTS’ INTELLECTUAL AND PRACTICAL SKILLS IN ZIKA LESSONS - Husenova, Makhliyo Sayfulloyevna; Nazarov, Erkin Sadikovich (Innovative Development in Educational Activities, 2023)
The content of the article is to develop intellectual and practical skills of students with the help of basic and science-related competencies in teaching physics and astronomy in general secondary schools.